Performance analysis of SLA - QoS UPE Metro Ethernet / Akmarul Nizam Zainudin - Zainudin, Akmarul Nizam (2014)
A Service Level Agreement (SLA) between a service provider and its customers will assure customers that they can get the service they pay for and will obligate the service provider to achieve its service promises. Failing to meet SLAs could result in serious financial consequences for a provider. Hence, service providers are interested in gaining a good understanding of the relationship between what they can promise in an SLA and what their IT infrastructure is capable of delivering. Similarly, consumers are interested in understanding the impact of the SLAs they sign on their own productivity. In this paper, we analyze to find the good measurement and method to achieve some results of QoS for customer satisfaction and with follow the standards. This thesis presented several measurement parameter techniques to verify the guaranteed QoS in UPE Metro Ethernet for customer satisfaction based on the acceptable standard values.